2020
DOI: 10.1590/0101-60830000000224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep quality of patients with panic disorder and generalized anxiety disorder during remission: a case-control study

Abstract: Background: Sleep disorders are common in psychiatric diseases. Panic disorder (PD) and generalized anxiety disorder (GAD) are two major anxiety disorders that are associated with sleep disorders. Objective: We hypothesized that poor sleep quality continues in PD and GAD during remission. Therefore, in this study we aimed to compare the sleep quality of patients with PD and GAD to that of healthy controls. Methods: The study included patients with PD (n = 42) and GAD (n = 40) who had been in remission for at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…It is well known that different instruments used This study found a significant relationship between anxiety and sleep quality among respondents. The result of this study was consistent with Hacimusalar and Karaaslan's (2019) 4 study that was conducted to GAD and panic disorder patients in a psychiatric clinic. GAD has the strongest relationship with poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is well known that different instruments used This study found a significant relationship between anxiety and sleep quality among respondents. The result of this study was consistent with Hacimusalar and Karaaslan's (2019) 4 study that was conducted to GAD and panic disorder patients in a psychiatric clinic. GAD has the strongest relationship with poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…22, 23 Moreover, sleep quality does not improve in GAD patients that are in remission. 4 Patients with panic disorder tend to have unexpected panic attacks during sleep and may increase sleep latency, decrease sleep duration, increase daytime sleepiness and sleep disturbances. Panic disorder is also commonly comorbid with depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep and anxiety have been shown to be significantly correlated in adolescents (( Jamieson, Broadhouse, Lagopoulos, et al, 2020 ); Tarokh et al, 2016 ). Reduced sleep is a criteria of the worry-centric generalized anxiety disorder ( APA, 2013 ), and reduced sleep quality has been associated with higher scores on the Beck Scale for Suicidal Ideation (SSI) ( Lee, Cho, Cho, & Kim, 2012 ), as well as the Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) ( Hacimuslar & Karaaslan, 2020 ). In a recent prospective study, participants who were rated as poor sleepers prior to chronic exposure to stressful circumstances (i.e.…”
Section: Introductionmentioning
confidence: 99%